Medienwirkungen beim Lernen am Beispiel des Vokabellernens - Giessen, Hans (Glottodidactica, 2013)
This study describes an experiment in vocabulary learning. The vocabulary was presented to students in two different forms, the classical one (a list of vocabulary presented on a paper sheet), and a computer-generated one (to guarantee validity: with the same list as shown on the paper sheet). No other variables have influenced learning. The remembrance of the vocabulary was tested immediately after, one day after and one week after learning. The results: Vocabulary remembrance was strikingly worse when learning from the computer screen in comparison with learning the classical way, from the paper sheet.